Pengaruh AI-Powered Chatbots terhadap Writing Proficiency: Studi pada Pembelajaran English as a Foreign Language (EFL) - Avradya Mayagita; Uswatun Hasanah; Etik Dwi Styaningrum; Leny Hikmah Rentiana; Retno Dwigustini (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study aims to examine the effect of AI-powered chatbots on writing proficiency and to analyze the mediating role of writing motivation in English as a Foreign Language (EFL) learning. This research employed an explanatory quantitative approach using a survey design involving 100 EFL students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings show that AI-powered chatbots have a positive and significant effect on writing motivation and writing proficiency. Writing motivation also positively affects writing proficiency and partially mediates the relationship between AI-powered chatbots and writing proficiency. These results indicate that AI chatbots support EFL writing by providing immediate feedback, helping students develop ideas, improve grammar, enrich vocabulary, organize paragraphs, and increase confidence in revising their writing. The implication of this study is that EFL teachers and institutions should integrate AI-powered chatbots ethically and pedagogically to enhance students’ writing motivation and writing quality.